Are organic falls bridging reduced environments in the deep sea?: Results from colonization experiments in the Gulf of Cadiz - Cunha, MR (2015)
Organic falls create localised patches of organic enrichment and disturbance where enhanced degradation is mediated by diversified microbial assemblages and specialized fauna. The view of organic falls as “stepping stones” for the colonization of deep-sea reducing environments has been often loosely used, but much remains to be proven concerning their capability to bridge dispersal among such environments. Aiming the clarification of this issue, we used an experimental approach to answer the following questions: Are relatively small organic falls in the deep sea capable of sustaining taxonomically and trophically diverse assemblages over demographically relevant temporal scales Are there important depth- or site-related sources of variability for the composition and structure of these assemblages? Is the proximity of other reducing environments influential for their colonization? We analysed the taxonomical and trophic diversity patterns and partitioning (α- and β-diversity) of the macrofaunal assemblages recruited in small colonization devices with organic and inorganic substrata after 1-2 years of deployment on mud volcanoes of the Gulf of Cádiz. Our results show that small organic falls can sustain highly diverse and trophically coherent assemblages for time periods allowing growth to reproductive maturity, and successive generations of dominant species. The composition and structure of the assemblages showed variability consistent with their biogeographic and bathymetric contexts. However, the proximity of cold seeps had limited influence on the similarity between the assemblages of these two habitats and organic falls sustained a distinctive fauna with dominant substrate-specific taxa. We conclude that it is unlikely that small organic falls may regularly ensure population connectivity among cold seeps and vents. They may be a recurrent source of evolutionary candidates for the colonization of such ecosystems. However, there may be a critical size of organic fall to create the necessary intense and persistent reducing conditions for sustaining typical chemosymbiotic vent and seep organisms.